Towards a european heritage diversity: geosites on the galician coast (NW Spain) - Costa-Casais, Manuela (2016)
The pervasive lack of awareness in today’s society regarding geological processes and their effects on the landscape is of such magnitude that their relationship to biodiversity and their value as part of the natural heritage is almost completely ignored. In this situation are the Quaternary deposits located on the Galician coast (NW Spain). The lack of awareness of these deposits, or the mere fact that they have either been omitted, or included as other coastal formations in the POL (The Planning Programme for Coastal areas of Galicia), makes their recognition and promotion unfeasible. Taking into account the scientific works and considering the current administrative context, the aim of this study is to demonstrate the importance and scientific and educational interest of the Quaternary sedimentary deposits as palaeoenvironmental records in the hope that this will be recognised as a Geosites by administration, in order to promote their geoconservation as a meaningful and diverse Geological Heritage in European Coastal context.